2016
DOI: 10.1101/gad.274183.115
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular mechanism directing nucleosome reorganization by human FACT

Abstract: Facilitates chromatin transcription (FACT) plays essential roles in chromatin remodeling during DNA transcription, replication, and repair. Our structural and biochemical studies of human FACT-histone interactions present precise views of nucleosome reorganization, conducted by the FACT-SPT16 (suppressor of Ty 16) Mid domain and its adjacent acidic AID segment. AID accesses the H2B N-terminal basic region exposed by partial unwrapping of the nucleosomal DNA, thereby triggering the invasion of FACT into the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
200
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(220 citation statements)
references
References 63 publications
20
200
0
Order By: Relevance
“…Spt16 can bind H2A/H2B dimers in vivo and in vitro and H3/H4 tetramers in vitro but with higher specificity for H2A/H2B (30,(33)(34)(35)(36)(37). Recently it was demonstrated that the middle domain of human Spt16 interacts with the H3/H4 tetramer, and the AID domain interacts with H2B (38). The best studied transcriptional role for Spt16 involves the catalysis of nucleosomal reorganization during transcriptional elongation (25, 39 -41).…”
mentioning
confidence: 99%
“…Spt16 can bind H2A/H2B dimers in vivo and in vitro and H3/H4 tetramers in vitro but with higher specificity for H2A/H2B (30,(33)(34)(35)(36)(37). Recently it was demonstrated that the middle domain of human Spt16 interacts with the H3/H4 tetramer, and the AID domain interacts with H2B (38). The best studied transcriptional role for Spt16 involves the catalysis of nucleosomal reorganization during transcriptional elongation (25, 39 -41).…”
mentioning
confidence: 99%
“…4A; Hondele et al 2013). Recent structural analyses of the S. cerevisiae Spt16-CTD:H2A-H2B complex has challenged the role of the Spt16-MD U-turn in targeting H2A-H2B and instead revealed that the primary H2A-H2B-binding site exists within the acidic Spt16-C and Pob3-C (SSRP1) domains (Kemble et al 2015), a conclusion independently validated by others (Tsunaka et al 2016). Interestingly, the minimal region of Spt16 that binds H2A-H2B (S965-E990 in S. cerevisiae) (Kemble et al 2015) corresponds to approximately the same region of human Spt16 (Spt16 956-960), which we identified to bind to CENP-T/-W.…”
Section: Spt16 Can Bind Either H2a-h2b or Cenp-t/-wmentioning
confidence: 94%
“…The region of Spt16 that is sufficient to bind CENP-T/-W (Spt16 amino acids 956-960) is within the minimum region of S. cerevisiae Spt16 (amino acids 958-999), determined to be sufficient to bind H2A-H2B (Kemble et al 2015). No H2A-H2B binding by the Spt16MD domain was detected with either yeast or human Spt16 (Kemble et al 2015;Tsunaka et al 2016), and, similarly, we did not find any binding between the human Spt16MD domain (amino acids 650-933) and CENP-T HFD /-W. The interaction between CENP-T/-W and FACT excludes the interaction between FACT and H2A-H2B and exhibits distinct properties.…”
Section: Fact Regulates In Vivo Dynamics Of Cenp-t/-wmentioning
confidence: 99%
“…More importantly, genomic analyses showed that FACT destabilizes the N/N+2 Micro-C interactions (tetranucleosomal motifs) to facilitate gene transcription in yeast. Distinct domains of FACT have been shown to interact with H2A/H2B or H3/H4 separately (Stuwe et al 2008;Zhang et al 2015;Tsunaka et al 2016), suggesting that these distinct domains of FACT might be responsible for their different activities in remodeling the nucleosome and/or the tetranucleosomal unit. It will be of great interest to generate a series of FACT mutants to resolve the distinctive activity in remodeling the nucleosome and/or the tetranucleosome using singlemolecule measurements.…”
Section: Epigenetic Regulation Of Chromatin Fibers By Chromatin Factorsmentioning
confidence: 99%